MPROVING THE QUALITY OF FUTURE PRIMARY IT TEACHER TRAINING MODEL - Soatmurodovich, O'tkir Eshaliyev (Journal of Higher Education and Academic Advancement, 2024)
The article examines the experience of using the adaptive model of teaching informatics and digital technologies. The impact of the adaptive model on improving the quality of education and forming the professional component of future informatics teachers was analyzed